Osmanlı kanunnâmeleri ve hukukî tahlilleri - Akgündüz, Ahmed, 1955- (İstanbul)
10 c. (710 s., [2] s. harita ; 655 s. ; 567 s. ; 780 s. ; 774 s. ; 812 s. ; 896 s. ; 733 s. ; 736 s. ; 1022 s. ; 1017 s.)